A study on factors influencing consumer perception on general insurance - KRISHNAMOORTHY, MR. D.; JAYAKUMAR, MS SANDRA K (The journal of contemporary issues in business and government, 2020)
The world is changing everyday with that the risk and uncertainties also increases. The research paper titled ‘A study on consumer perception on general insurance’. The objective of this study is to analyse factors which affects the consumer perception on general insurance. The research design used in this study is descriptive research design and the technique used is Simple random technique. The sample size of this study is 110 respondents and primary data is used. The tools used for this study are Frequency analysis, Mean analysis, Independent T test and ANOVA. In this study we found that there is a significant difference among Age, Education and Occupation with respect to consumer perception towards insurance policy and there is no significant difference among income with respect to consumer perception towards insurance policy. We can conclude that Appropriate and Timely service, Reliability of the company, Quality of service, Customers convenience and Relationship with customer are the factors which affect the consumer perception towards General Insurance.